Against Normative Defeat. Issue 520 (6th January 2021) - Nottelmann, Nikolaj
Abstract: Several epistemologists have advanced the idea that a subject's epistemic status can be weakened by evidence she does not possess but should have possessed, or, alternatively, by beliefs or doubts she should have had under her evidential circumstances but does not have. This alleged phenomenon is known as normative defeat and its adherents have typically reported intuitions that it obtains under mundane circumstances. Some epistemologists have analyzed normative defeat in terms of breached epistemic obligations, while others have preferred an analysis in terms of cognitive malfunctioning. No matter which analysis one prefers, I here argue that - given plausible psychological and epistemological assumptions - if the normative defeat phenomenon were real it would be more bizarre than is generally recognized. I conclude that alleged cases of normatively defeated knowledge or epistemic justification are better analyzed as cases of lucky or undeserved knowledge or epistemic justification.